The Courtship of Lancaster County: Minding Molly - Book 3 - Gould, Leslie, 1962- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2014)
"In this contemporary Amish romance, Molly Zook's latest attempt to control her fate backfires. Will she finally learn to trust God with her life--and with her future groom?"--
Keywords: Amish -- Fiction; Man-woman relationships -- Fiction; Lancaster County (Pa.) -- Fiction; Love stories; Christian fiction